1999
DOI: 10.1016/s0002-9440(10)65204-2
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Regulates the Expression of the Matrix Metalloproteinase-7 in Human Colorectal Cancer

Abstract: Most colorectal cancers have loss of function mutations in the adenomatosis polyposis coli (APC) tumor suppressor gene. This leads to accumulation of beta-catenin, which together with the DNA binding protein TCF-4 functions as a transcriptional activator. Recently defined target genes are c-myc and cyclin D1, linking the APC gene defect to the capacity for autonomous proliferation of colon tumors. Here we report the identification of the matrix metalloproteinase MMP-7 as another target gene of beta-catenin/TCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
462
1
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(488 citation statements)
references
References 26 publications
14
462
1
11
Order By: Relevance
“…(Brabletz et al, 1998). Although we found a significant correlation between nuclear beta-catenin expression and ulcerative growth and also observed that most of the ulcerative tumours were rectal carcinomas (Table 1), we did not observe a significant relationship between tumour localisation and nuclear (He et al, 1998), cyclin D1 (Tetsu and McCormick, 1999), gastrin (Koh et al, 2000), PPARS (He et al, 1999) MMP-7 (Brabletz et al, 1999;Crawford et al, 1999) are warranted. Some factors such as c-myc, cyclin D and gastrin reportedly relate to tumour proliferation, while others are related to tumour invasion.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…(Brabletz et al, 1998). Although we found a significant correlation between nuclear beta-catenin expression and ulcerative growth and also observed that most of the ulcerative tumours were rectal carcinomas (Table 1), we did not observe a significant relationship between tumour localisation and nuclear (He et al, 1998), cyclin D1 (Tetsu and McCormick, 1999), gastrin (Koh et al, 2000), PPARS (He et al, 1999) MMP-7 (Brabletz et al, 1999;Crawford et al, 1999) are warranted. Some factors such as c-myc, cyclin D and gastrin reportedly relate to tumour proliferation, while others are related to tumour invasion.…”
Section: Discussionmentioning
confidence: 47%
“…Some factors such as c-myc, cyclin D and gastrin reportedly relate to tumour proliferation, while others are related to tumour invasion. MMP-7 is regulated by b-catenin expression (Brabletz et al, 1999) and is a proteolytic enzyme related to tumour invasion. It may well be reasonable to relate proteolysis to ulcerative growth.…”
Section: Discussionmentioning
confidence: 99%
“…LEF1 (Hovanes et al, 2001), MMP7 (Brabletz et al, 1999), cyclin D1 (Tetsu and McCormick, 1999) and CD44 (Wielenga et al, 1999) are all reported to be direct or indirect targets of b-catenin-TCF/LEF, confirming that Wnt signaling is blocked by SFRP2 in SNU638 cells (Table 2). We also found that significant numbers of genes related to cellular proliferation, growth or apoptosis are repressed or induced by SFRP2.…”
Section: Changes In Gene Expression Profiles Induced By Overexpressiomentioning
confidence: 68%
“…), some of them having important implications in cancer progression. [27][28][29][30][31][32][33][34][35][36] These independent data from the literature therefore suggest that a reorganisation of E-cadherin/b-catenin and an overexpression of MCP-1 in tumour cells are 2 events associated with cancer progression. This prompted us to investigate the potential regulation of MCP-1 by the b-catenin/TCF pathway.…”
mentioning
confidence: 99%